Kebijakan Hukum Tindak Pidana Pencurian Sepeda Motor Dengan Tindak Kekerasan - Zainudin Hasan; Phanizar Cahaya Saputra; Lucky Arijano Augusta Putra; Muhammad Daud Aulia Ramadhan Indrajaya (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2023)
According to data collected by Bandar Lampung Police, between the beginning of the year and the end of 2022, officers handled 2,898 incidents, including 502 reports of motor vehicle theft, 247 reports of theft with aggravation, and 78 reports of theft with violence. The purpose of this article is to describe the legal policy of violent motorcycle theft. This research is a normative legal research, in this research the elements of the crime of theft with violence as formulated in Article 365 of the Criminal Code are studied. The results showed that a person who commits the crime of motorcycle theft with violence can be caught under Article 356 of the Criminal Code. In this case, the factors that cause a person to commit a violent motorcycle theft are economic factors, social environment, opportunity, and less than optimal law enforcement.